Safety and efficacy of rapid dose administration of quetiapine in bipolar mania - Hatim, A.; Habil, H.; Jesjeet, S.G.; Low, C.C.; Joseph, J.; Jambunathan, S.T.; Zuraida, N.Z. (2006)
in this open-label pilot study, 20 adult patients hospitalized for acute bipolar mania received oral quetiapine as a single evening dose of 200 mg on day 1, increased by 200 mg/day on days 2, 3, and 4 until 800 mg/day taken in 2 divided doses on day 4. From day 5 onward, patients received a flexible total dose of 400-800mg/day until completion of 3 weeks of treatment. Safety and tolerability were assessed by adverse-event (AE)-related dropouts in week 1, incidence of AEs including EPS, changes in electrocardiogram, and vital signs. Efficacy was assessed using the YMRS, PANSS, and CGI scales. Nineteen of 20 patients (95) completed the quetiapine rapid titration during week 1. Significant improvement was observed in YMRS, PANSS, and CGI Severity of Illness scores by day 5, and was maintained throughout the study. A reduction of >= 50 in YMRS score was achieved by 75 of patients by day 7, and maintained to day 21. Overall, 20 of patients discontinued due to AEs. Agitation was the most common cause of AE-related study discontinuation. Thirty-five per cent of patients required dose adjustment due to AEs after rapid dose administration was completed. Most patients tolerated rapid titration of quetiapine to 800 mg/day by day 4 of therapy, with a significant improvement in manic symptoms by day 7 of treatment. Copyright (c) 2006 John Wiley & Sons, Ltd.